Propofol modulates glycolysis reprogramming of ovarian tumor via restraining circular RNA-zinc finger RNA-binding protein/microRNA-212-5p/superoxide dismutase 2 axis. Issue 5 (2nd May 2022) - Qu, DongDong; Zou, Xin; Liu, ZhiLin
ABSTRACT: Metabolic reprogramming refers to the transformation of the whole metabolic network covering glycolysis and mitochondrial metabolism, which is primarily manifested as the Warburg effect and mitochondrial metabolic reprogramming. Propofol (Pro) has been testified to suppress the malignancy of diversified human cancers. Nevertheless, its role in glycolysis is still uncertain. The purpose of this study was to determine whether Pro modulated glycolysis in ovarian cancer (OC) cells. Cell proliferation, apoptosis, migration, and invasion were tested via CCK-8, flow cytometry, and Transwell assays, respectively, and glucose intake, lactic acid, and ATP production were also determined. Pro restrained glycolysis via mediating the circular RNA-zinc finger RNA-binding protein (ZFR)/microRNA (miR)-212-5p/superoxide dismutase 2 (SOD2) axis. Additionally, Pro restrained cancer cell advancement via modulating circ-ZFR/miR-212-5p/SOD2 axis. In short, Pro restrained glycolysis via mediating the circ-ZFR/miR-212-5p/SOD2 axis. These results offered a better theoretical foundation for comprehending the molecular pathology of OC and provided a novel target for OC diagnosis and treatment. Graphic abstract: uf0001